2015
DOI: 10.18382/jraam.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Model Akuntabilitas Organisasi Non Profit pada Masjid

Abstract: Tanggal masuk 17-12-2014 The purpose of this study is to examine accountability model for mosque and its relation to organisational culture and organisational learning. Data were collected from 60 mosques located in Padang through distributed questionaire to mosques' managers. Findings reveal that only internal accountability positively significant affects organisational culture and organisational learning. While upward accountability significantly does not affect organisational culture which implies that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…Pengelolaan organisasi sebaik mungkin tentu menjadi sangat penting dalam upaya mencapai visi lembaga (Siskawati, -, and Surya 2015). Pengolahan yang salah akan menyebabkan terjadinya kegagalan dan dapat berdampak pada berakhirnya organisasi tersebut.…”
Section: Cerdasunclassified
“…Pengelolaan organisasi sebaik mungkin tentu menjadi sangat penting dalam upaya mencapai visi lembaga (Siskawati, -, and Surya 2015). Pengolahan yang salah akan menyebabkan terjadinya kegagalan dan dapat berdampak pada berakhirnya organisasi tersebut.…”
Section: Cerdasunclassified
“…Namun kritik terhadap akuntabilitas masjid mengatakan bahwa pengendalian internal dan pengawasan pengelolaan keuangan pada organisasi masjid masih lemah (Mohamed, Aziz, Masrek, & Daud, 2014). Hal Ini juga dikaitkan dengan kinerja masjid terhadap pengelolaan kegiatan masjid yang tidak efektif dan rendahnya profesionalitas pengurus dalam hal tata kelola (Siskawati, 2015). Akuntabilitas pada organisasi nonprofit hingga saat ini masih di dominasi oleh rasionalisasi hubungan principal-agent.…”
Section: A Latar Belakangunclassified
“…The context of this study is focused on the Al Ikhlas mosque in Gorontalo Indonesia. The present research focused on capital accounting studies on non-profit organizations, namely mosques because so far, accounting studies in the context of mosques have been carried out in the previous studies (Azwari, 2018;Kurniasari, 2011;Siskawati et al, 2016;Siskawati & Surya, 2015). However, some of these studies have not revealed how local wisdom values shape accounting practices in mosques.…”
Section: Introductionmentioning
confidence: 99%